Acid-functionalized nanoparticles for biomass hydrolysis - Peña Duque, Leidy Eugenia (Kansas State University, 2013)
Cellulosic ethanol is a renewable source of energy. Lignocellulosic biomass is a complex material composed mainly of cellulose, hemicellulose, and lignin. Biomass pretreatment is a required step to make sugar polymers liable to hydrolysis. Mineral acids are commonly used for biomass pretreatment. Using acid catalysts that can be recovered and reused could make the process economically more attractive. The overall goal of this dissertation is the development of a recyclable nanocatalyst for the hydrolysis of biomass sugars. Cobalt iron oxide nanoparticles (CoFe[superscript]2O[subscript]4) were synthesized to provide a magnetic core that could be separated from reaction using a magnetic field and modified to carry acid functional groups. X-ray diffraction (XRD) confirmed the crystal structure was that of cobalt spinel ferrite. CoFe[superscript]2O[superscript]4 were covered with silica which served as linker for the acid functions. Silica-coated nanoparticles were functionalized with three different acid functions: perfluoropropyl-sulfonic acid, carboxylic acid, and propyl-sulfonic acid. Transmission electron microscope (TEM) images were analyzed to obtain particle size distributions of the nanoparticles. Total carbon, nitrogen, and sulfur were quantified using an elemental analyzer. Fourier transform infra-red spectra confirmed the presence of sulfonic and carboxylic acid functions and ion-exchange titrations accounted for the total amount of catalytic acid sites per nanoparticle mass. These nanoparticles were evaluated for their performance to hydrolyze the β-1,4 glycosidic bond of the cellobiose molecule. Propyl-sulfonic (PS) and perfluoropropyl-sulfonic (PFS) acid functionalized nanoparticles catalyzed the hydrolysis of cellobiose significantly better than the control. PS and PFS were also evaluated for their capacity to solubilize wheat straw hemicelluloses and performed better than the control. Although PFS nanoparticles were stronger acid catalysts, the acid functions leached out of the nanoparticle during the catalytic reactions. PS nanoparticles were further evaluated for the pretreatment of corn stover in order to increase digestibility of the biomass. The pretreatment was carried out at three different catalyst load and temperature levels. At 180°C, the total glucose yield was linearly correlated to the catalyst load. A maximum glucose yield of 90% and 58% of the hemicellulose sugars were obtained at this temperature.
Keywords: Nanoparticles; Pretreatment; Biomass; Engineering (0537)